Analisis Dampak Otomasi Industri terhadap Efisiensi Operasional dan Optimasi Konsumsi Energi - Resa Pramudita; Muhammad Adzi Putra Ramadhan; Muhammad Rama Ashari; Raditya Arya Nafisa; Dita Nur Rahmawati (Universitas Widyatama, 2024)
This study examines the impact of industrial automation and technological advancements, such as artificial intelligence (AI), robotics, and the Internet of Things (IoT), on work efficiency, resource management, and workforce demands in the era of Industry 4.0. The findings reveal that automation enhances productivity by up to 30%, reduces material waste, and supports sustainability through the adoption of renewable energy. However, the replacement of manual jobs by technology creates challenges in meeting the demand for new skills. Education and training are strategic solutions through the integration of STEM-based curricula, reskilling programs, and upskilling initiatives. Additionally, automation contributes to building environmentally friendly production systems by optimizing energy use and improving waste management. Collaboration between governments, private sectors, and educational institutions is crucial to ensure that automation not only improves efficiency and productivity but also creates new opportunities in the technology sector. This study highlights the importance of technological adaptation and human resource development to address challenges and capitalize on opportunities in the era of Industry 4.0.